THE COMPARISON OF SENSITIVITY Salmonella typhi BACTERIA IN ISOLATE OF PATIENTS WITH THYPHOID FEVER AND PURE CULTURE ON SOME ANTIBIOTICS AT LABORATORY - NORMA FARIZAH FAHMI (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2019)
Typhoid fever is one of infectious diseases which can cause many problems in Indonesia and other developing countries. This fever occurs as a result of infections triggered by Salmonella typhi bacteria. The growth of Salmonella typhi can be inhibited using antibiotics. This study aims at investigating whether there is a difference in sensitivity test of Salmonella typhi bacteria in isolate of patients with typhoid fever and pure culture in laboratoryonsome antibiotics. Salmonella typhi bacteria were isolated typhoid fever suspects at one of hospitals in Surakarta. Pure cultures of Salmonella typhi bacteria were obtained from Microbiological Laboratory of Setia Budi University. Sensitivity test of antibiotics on Salmonella typhi bacteria used diffusion method. Data of antibiotics of inhibition zone diameter (mm) of antibiotics were analyzed statistically using Two-Way Anova test. The research results demonstrate that the sensitivity test on Salmonella typhi bacteria in isolate of patients with typhoid fever shows resistance (R) towards amoxicillin and sensitivity (S) towards trimethoprim, chloramphenicol, gentamicin, ciprofloxacin. Meanwhile, pure culture shows sensitivity (S) towards trimethoprim, chloramphenicol, gentamicin, amoxicillin, ciprofloxacin. The diameter of inhibition zone of patient isolate is smaller than that of pure culture.